SPATIAL PLANNING AND PRACTICE IN LATVIA - Ezmale, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The current system of territorial planning in Latvia has been formed after regaining its independence in 1991. The European Union has had a great impact on the development of the concept and practice of spatial planning throughout the entire Europe and in each of the Member States, including Latvia. The common planning activities and initiatives at the European level had influenced planning practice in all the Member States.  The aim of the research is to describe the development of the spatial planning system, as well as the features of planning practice in Latvia in the context of spatial planning activities at the European Union level. During the research, the author describes the development of the spatial planning concept, the typology and system of spatial planning in the European Union. Additionally, the author characterises the development of the legal framework for and practice in the spatial planning system of Latvia, as well as identifies the features of the Latvian spatial planning system and practice in the context of spatial planning activities at the European Union level. Research methods – content analysis, deductive and inductive methods, theoretical analysis of scientific literature, EU and Latvian legislation analysis, comparative analysis, etc.